2007
DOI: 10.2174/187425640701011046
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Exposure to Marketed Milk with Antimicrobial Drug Residues in Ghana

Abstract: Abstract:The study was carried out to determine the extent to which antimicrobial drugs may be translocated into milk and the associated risk of exposure by consumers. A total of 394 milk samples were collected in the study sites in dry and wet seasons, and from different categories of milk market agents, including producers (farmers), processors, wholesalers (assemblers) and retailers. The milk samples were screened for antimicrobial drug residues using the Charm Aim-96 antimicrobial inhibition assay screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…Also, the results of the evaluation of tetracycline and oxytetracycline residues in milk samples in Tehran province indicated that above 8.7% of milk samples were positive for antibiotic residues (Rassouli et al, 2010). In Ghana, Aning et al (2007) reported on the analysis of raw milk samples (394 samples) marketed in two major cities, Accra and Kumasi. Thirty-five percent of the samples were contaminated with one or more of the five families of antibiotics (βetalactams, tetracycline, aminoglycosides, macrolides and sulphonamides) screened.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results of the evaluation of tetracycline and oxytetracycline residues in milk samples in Tehran province indicated that above 8.7% of milk samples were positive for antibiotic residues (Rassouli et al, 2010). In Ghana, Aning et al (2007) reported on the analysis of raw milk samples (394 samples) marketed in two major cities, Accra and Kumasi. Thirty-five percent of the samples were contaminated with one or more of the five families of antibiotics (βetalactams, tetracycline, aminoglycosides, macrolides and sulphonamides) screened.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Brazil, a study to assess hazards in unpasteurized marketed milk at farm level found a prevalence of antimicrobial residues of 11.5% [ 29 ]. A study in the peri-urban areas of Accra and Kumasi cities in Ghana [ 14 ] found that 35.5% of samples of raw marketed milk, collected from different marketing agents including farmers, processors, wholesalers and retailers, were contaminated with antimicrobial residues. In Tanzania, a prevalence of 36% was observed in a study to investigate the risk of exposure to antimicrobial residues present in marketed raw milk in Mwanza and Dar es Salaam [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, quality and safety of milk is regulated by the Dairy Industry Act [ 11 ], Public Health Act [ 12 ] and the Standards Act [ 13 ]. However, such regulations might not be adhered to or enforced, as is the case in many developing countries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of antibiotic residues in milk constitutes a danger for the consumer by provoking the development of resistance to antibiotics by promoting the emergence of a multiresistant microflora. It may December lencher toxic accidents or even rarely allergic disorders [2]. The problem of residues can also be the cause of the total or partial inhibition of fermentation phenomena of bacterial origin in dairy products such as yoghurts and cheeses, which represents an economic loss for the dairy industry.…”
Section: Introductionmentioning
confidence: 99%